Analysis of National Pharmacovigilance Data Associated with Statin Use in Korea. Issue 5 (22nd June 2017) - Kim, Hyunah; Kim, Namhyo; Lee, Da Hee; Kim, Hun‐Sung
Abstract: The aim of this study was to evaluate clinical manifestations, age distribution and risk factors of adverse drug reactions (ADRs) of statins. Korean Adverse Event Reporting System (KAERS) database records (July 2009–June 2014) on statin‐treated adults were used. ADRs classified as 'certain', 'probable' and 'possible' based on the WHO‐Uppsala Monitoring Centre criteria were analysed. The frequency of ADRs was compared between adults (18–64 years) and older people (age ≥65 years) groups. In total, 2161 ADRs from 1690 patients (579, 34.3% older people) were included for analysis. Mean patient age and ADRs per patient were 60.46 ± 12.72 years and 1.28, respectively. ADRs were reported with atorvastatin (48.4%), rosuvastatin (23.0%), pitavastatin (10.4%) and simvastatin (9.1%). The frequent ADRs were gastrointestinal (421 events, 19.5%), musculoskeletal (331, 15.3%), skin (312, 14.4%) and hepatobiliary disorders (286, 13.2%). Skin disorders were significantly more frequent in adults compared to those in older patients (16.3% versus 12.4%, p = 0.021). Common clinical symptoms were myalgia (263 events, 12.2%), dyspepsia (133, 6.2%) and pruritus (103, 4.8%). Myalgia was more frequently reported in adults (12.7% versus 9.5%, p = 0.039) and dizziness was more frequent in older people (3.4% versus 5.8%, p = 0.015). According to KAERS data, leading statin ADRs were gastrointestinal and musculoskeletal disorders. Myalgia and dyspepsia were the common clinical symptoms.